Mechanisms of disordered neurodegenerative function: concepts and facts about the different roles of the protein kinase RNA-like endoplasmic reticulum kinase (PERK) - Taalab, Yasmeen M.; Ibrahim, Nour; Maher, Ahmed; Hassan, Mubashir; Mohammad, Wael; Moustafa, Ahmed A.; Salama, Mohamed M.; Johar, Dina R.; Bernstein, Larry H. (De Gruyter, 2018)
Neurodegenerative diseases, such as Alzheimer's disease, Huntington's disease, Parkinson's disease, prion disease, and amyotrophic lateral sclerosis, are a dissimilar group of disorders that share a hallmark feature of accumulation of abnormal intraneuronal or extraneuronal misfolded/unfolded protein and are classified as protein misfolding disorders. Cellular and endoplasmic reticulum (ER) stress activates multiple signaling cascades of the unfolded protein response (UPR). Consequently, translational and transcriptional alterations in target gene expression occur in response directed toward restoring the ER capacity of proteostasis and reestablishing the cellular homeostasis. Evidences from in vitro and in vivo disease models indicate that disruption of ER homeostasis causes abnormal protein aggregation that leads to synaptic and neuronal dysfunction. However, the exact mechanism by which it contributes to disease progression and pathophysiological changes remains vague. Downstream signaling pathways of UPR are fully integrated, yet with diverse unexpected outcomes in different disease models. Three well-identified ER stress sensors have been implicated in UPR, namely, inositol requiring enzyme 1, protein kinase RNA-activated-like ER kinase (PERK), and activating transcription factor 6. Although it cannot be denied that each of the involved stress sensor initiates a distinct downstream signaling pathway, it becomes increasingly clear that shared pathways are crucial in determining whether or not the UPR will guide the cells toward adaptive prosurvival or proapoptotic responses. We review a body of work on the mechanism of neurodegenerative diseases based on oxidative stress and cell death pathways with emphasis on the role of PERK.